Assessing Laboratory Behavior in Genetic Practicals: A Study on Pre-Service Biology Teachers - Kharomah, Sinta; Susanto, Hendra; Zubaidah, Siti (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
Laboratory behavior refers to attitudes and actions in the laboratory, including planning and design, manipulative skills, conducting experiments, observation and data recording, data interpretation, and responsibility, initiative, and work habits. Laboratory behavior plays an essential role in the development of experimental skills, especially in Genetics courses. This study aims to describe the laboratory behavior of biology education students (N=99) who have taken the Genetics course. The study uses a quantitative descriptive approach using self-assessment questionnaires, peer assessments, observation sheets, and practical report rubrics. The scores from the four assessment sources were averaged equally, with each source contributing the same weight to the final score. The results show that student laboratory behavior falls into the "Needs Improvement" category, with an average achievement percentage of 62.50%. The average achievement percentages for each indicator are as follows: planning and design, 62.57%; experiment implementation, 62.35%; observation and data recording, 59.22%; data interpretation, 59.31%; and responsibility, initiative, and work habits, 64.71%. These results indicate that students' laboratory behavior needs improvement and should be enhanced through effective practical learning, supported by learning models and media that are appropriate to the needs and real situations in the laboratory.